(untitled) (Research, Society and Development, 2021)
Objective: The study aimed to analyze the occupational stress conditions in which the professionals of Oral Health Teams of the Sanitary District II of Recife are submitted. Methods: Cross-sectional descriptive study conducted with 66 Family Health Strategy dental professionals, analyzing stress and reward situations at work from the Effort-Reward questionnaire. Results: According to the calculation of the effort-reward imbalance ratio, 90.3% of the sample are in a balance between effort spent at work and reward received. However, 45.5% have high effort at work, 53% have low reward and 47% have high excessive commitment, which reveals a population that experiences situations of occupational stress and is prone to well-being disorders in the workplace. occupational health and health. Conclusion: The adoption of practices that strive for equal treatment and appreciation of professionals should be prioritized, in addition to the legitimation of surveillance and health care measures for workers in the municipality.